Infantile cortical hyperostosis (ICH) secondary to prostaglandin E1 infusion in a newborn with complex cyanotic heart disease: a case report - Subramaniam, Kishan Rao; Karupiah, Rajandra Kumar; Mor Japar Khan, Ed Simor Khan; Zakaria@Mohamad, Zamzuri (Crimson Publishers, 2018)
Infantile cortical hyperostosis (ICH), also known as Caffey’s disease, is a benign self-limiting condition affecting young infants. The initial symptom of the classical ICH is usually irritability, fever and soft tissue swelling affecting one or more bones. Diagnosis is usually delayed because its clinical presentation mimics many other clinical conditions such as osteomyelitis, scurvy, hypervitaminosis A, child abuse, bone tumor or even fracture. There are no laboratory tests to confirm the diagnosis. There are two types of ICH been described; the classical mild infantile form and the more severe prenatal form. Most of the cases of ICH are sporadic, but autosomal dominant and recessive patterns have been reported as well. It is linked with missense mutation in COL1A1, the gene encoding the α1 chain of type I collagen and has raised some doubts whether it is a type of collagen disorder, like osteogenesis imperfect. In this case, the newborn developed ICH due to prolonged infusion with prostaglandin E1 which was given in view of congenital cyanotic heart disease. Prostaglandin E1 infusion is used for maintaining the patency of ductus arteriosus in ductus dependent congenital heart defects in neonates and is usually administered before corrective heart surgery. ICH is mostly self-limiting and resolves within 12-24 months and usually does not require any treatment. Anti-inflammatory drugs such as NSAIDS(indomethacin and naproxen) and steroids has been used in symptomatic cases with success. The outcome is generally good with symptoms resolution usually before the age of one year. Relapses are uncommon.